Dynamic frequency hopping communities for efficient IEEE 802.22 operation. - Hu, Wendong (IEEE Communications magazine)
One of the key challenges of the emerging cognitive radio-based IEEE 802.22 wireless regional area networks (WRANs) is to address two apparently conflicting requirements: ensuring QoS satisfaction for WRAN services while providing reliable spectrum sensing for guaranteeing licensed user protection. To perform reliable sensing, in the basic operation mode on a single frequency band (non-hopping mode), one must allocate quiet times, that is, periodically interrupt data transmission that could impair the QoS of WRAN. This critical issue can be addressed by an alternative operation mode proposed in 802.22 called dynamic frequency hopping (DFH), where WRAN data transmission is performed in parallel with spectrum sensing without interruptions. DFH community, as described in this article, is a mechanism that coordinates multiple WRAN cells operating in the DFH mode, such that efficient frequency usage and reliable channel sensing are achieved. The key idea of DFH community is that neighboring WRAN cells form cooperating communities that coordinate their DFH operations.